Study of the quality of zabady drink made by different exopolysaccharides - El-Ghandour,A.A; Bakr,A.Sh.T; Mousa,M.A.M. (2009)
The quality of zabady drink made by using different exopolysaccharidesproducing cultures was investigated, Treatment I: Yo Mix 495 consisted of S. themophilus + L. bulgaricus, Treatment 11: Yo Mix 205 consisted of S. themophilus +L. acidophilus + Befedobacterium lactis, and Treatment lll: Star Six contained of S.themophilus were carried out, compared with control (conventional yoghurt starter +pectin). Resultant products were analyzed when fresh and afier storing for 14 days. These treatments had no effect on total solids, fat and protein contents, however acidity, pH, soluble nitrogen, acetaldehyde, TVFA contents and whey exuded were slightly increased and viscosity had an opposite trend with increasing the storage period. In treatment II zabady drink containing exopolysaccharides-producing cultures may contribute positively to the mouth-feel and had more desirable rheological properties, and taste, improved the functional characteristics and reduction of syneresis (wheying off), of zabady drink without the use of additives,. Treatment Il had the best quality because it contains mixed cultures which produced EPS at a faster rate
Includes reference.
Summary in Arabic.
Summary in Arabic.
1
Keywords: Yogurt drinks; Microbial exopolysaccharides